Tindak Tutur Ilokusi dalam Film ‘’Amelie Rennt (An Unexpected Friendship)’’ - Nilam Sandra Devi; Mantasiah R; Laelah Azizah (Phonologie : Journal of Language and Literature, 2022)
Abstract. This research aims to describe the types and functions of illocutionary speech acts in the film Amelie Rennt (an unexpected friendship). The data source of this research is the dialogue between characters in the film Amelie Rennt (an unexpected friendship) which was released in 2017 by Tobias Wiemann. This research is descriptive qualitative, data collection is done through the method of listening and noting. The validity and reliability of the data can be checked by interrater and intrarater. Data analysis using pragmatic equivalent technique. The data obtained were   then   classified   according   to   the speech act theory by Searle and Leech. The results show that 1) in the film Amelie Rennt (an unexpected friendship) there are five types of speech acts, namely directive, assertive, declarative, expressive, and commissive speech acts. 2) there are four illocutionary functions in the conversation between players in the film Amelie Rennt (an unexpected friendship), namely competitive, collaborative, conflictive and convivial.Keywords: Illocutionary Speech Acts, Film, Amelie Rennt